Unusual concurrence of heterotopic glial nodule of the scalp and congenital herpes simplex virus type‐2 infection. (2nd September 2013) - Marnerides, Andreas; Sirotkina, Meeli; Papadogiannakis, Nikos
Abstract: Heterotopic glial nodules are rare congenital cutaneous lesions; only 13 cases of scalp localized lesions of this kind are reported in the English medical literature. Herpes simplex virus is a rare cause of neonatal morbidity and mortality and is a rare cause of intrauterine infection. We report the first case of concurrent presence of a heterotopic glial nodule of the scalp and neonatal, in utero ‐acquired, fatal herpes simplex virus type‐2 infection.